Analytical–numerical modeling of journal bearings with non-Newtonian fluids and cavitation effects - Silva, Fabrício Vieira [UNESP]; Zanardi, Maurício Araújo; de Souza, Teófilo Miguel [UNESP] (Springer Nature, 2021)
The search for better performance in internal combustion engines and machines which use hydrodynamic journal bearings has motivated recent studies in lubrication field, with the application of computational fluid dynamics. The present study deals with the dynamics of some non-Newtonian fluids in short journal bearings, using the Newtonian, Herschel-Bulkley, and Bingham models. The main objective is to compare fluid pressure distribution, cavitation occurrence, and performance parameters, such as load-carrying capacity, friction force, and side leakage rate. The bearing equations were solved in a MATLAB program, based on the Reynolds equations, with discretization by the finite volume method and a cyclic Tri-Diagonal Matrix Algorithm solver. In all performance parameters, the Herschel-Bulkley and Bingham non-Newtonian fluids showed advantages when compared to Newtonian fluid.
Keywords: Cavitation; Fluid film lubrication; Hydrodynamic lubrication; Journal bearing